Adult Vaccination Knowledge, Attitudes, and Behavior in Rural Tamil Nadu: A Cross-Sectional Study - Narayanan, Kiruthika; Edward, Shanthi; Prasanth, Krishna (National Journal of Community Medicine, 2025)
Background: Adult vaccination is a crucial yet underutilized component of public health, especially in rural areas where access to healthcare services is limited. Inadequate awareness regarding adult immunization adversely impacts individual health, healthcare systems, and economic productivity. Objective: To assess the knowledge, attitude, and behavior related to adult vaccination among rural population, Tamil Nadu. Methods: A cross-sectional study conducted among 260 healthy adults (18 to 80 years) in rural Chengalpattu District, Tamil Nadu, used simple random sampling method. Data were collected using a pre-tested, structured, and validated self-administered questionnaire, focusing on adult vaccination knowledge, attitude, and behavior. Data analysis was performed using IBM SPSS version 25. Results: Among 260 participants, 41.9% were aged 18-40 years. Covid-19 vaccine had the highest knowledge level (77%). Logistic Regression showed literacy (AOR:4.95) and socioeconomic status (AOR:2.43) significantly associated with knowledge. Likewise, literacy (AOR:3.65) and socioeconomic status (AOR:3.53) were significantly associated with attitude towards adult vaccination (p <0.05). Conclusion: The study findings underscore education, occupation, and socioeconomic status have a significant impact on adult vaccination acceptance. Addressing barriers to immunization through awareness campaigns and policy interventions is critical to improving adult vaccine uptake in rural populations.